Application of Decision Support System Based On GUI to Determine The Best Mall In Manado City By Using ELECTRE Method - Kenedi Binowo; Altien Jonathan Rindengan; Benny Pinontoan (d\'Cartesian: Jurnal Matematika dan Aplikasi, 2018)
Mall is a shopping center that has numerous functions, and the mall has become a place of human survival, therefore this research is done to choose the best mall in Manado city which is Jumbo, Mega Trade Center, Manado Town Square, Mega Mall, and Multimart. The ELECTRE method is one of the multi-criteria decision-making methods based on the concept of outranking by using pairwise comparisons of alternatives based on each appropriate criterion.Â  The purpose of this research is to find out the best mall in Manado city based on ELECTRE method, and to find out the most important thing in designing GUI based application system. GUI is a decision support program in mathematics programs. From the research result using ELECTRE method can be known that the best mall in Manado city is Mega Mall, because from the best calculation result is (Alternative 4), where if indicates that alternative is the chosen alternative. The results of GUI-based applications it has been perform a result that the most important thing in the making is: There must be a place of input value, there should be an output display, and there should be execution buttons, and most importantly also that must create a coding in accordance with the programming language that can be read by mathematics programs.K e y w o r d s: Â Mall, ELECTRE Method, Decision Support System, GUI Application